English law in the age of the Black Death, 1348-1381 : a transformation of governance and law - Palmer, Robert C., 1947- (Chapel Hill ; London : The University of North Carolina Press, 1993)
Robert Palmer's pathbreaking study shows how the Black Death triggered massive changes in both governance and law in fourteenth-century England, establishing the mechanisms by which the law adapted to social needs for centuries thereafter. Palmer is the first scholar to relate these medieval legal changes to social and demographic developments. The Black Death killed one-third of the English population between 1348 and 1351. To preserve traditional society, the king's government aggressively implemented new punitive legal remedies as mechanisms for social control. The changes inaugurated included Statute of Laborers prosecutions, penal bonds, uses, trespass on the case, and assumpsit. The government's attempt to shore up traditional society in fact transformed it. English governance was legitimately extended to routine regulation of all workers, from shepherds to innkeepers, smiths, and doctors. The new cohesiveness of the ecclesiastical and lay upper orders, the increase in subject matter jurisdictions, the growth of the chancellor's court, and the acceptance of coercive contractual remedies made the Black Death in England a transformative experience for law and for governance. Based on all available legal records, Palmer's book presents a new interpretation and chronology of these important legal changes and also establishes a policy foundation. The footnotes and appendixes present additional information on church-state relations and on the history of various occupations.
pt. 1. The upper orders drew together into a more cohesive government -- pt. 2. To facilitate or coerce the upper orders to stand to their obligations -- pt. 3. And to coerce the lower orders to stand to their obligations -- pt. 4. Appendix 1. Regulating the church -- Appendix 2. The written contract -- Appendix 3. Carrier writs -- Appendix 4. Cutting timber -- Appendix 5. Builders -- Appendix 6. London doctors -- Appendix 7. Doctors of animals and people -- Appendix 8. Detinue of animals -- Appendix 9. Shepherd Assumpsit writs -- Appendix 10. Horses bailed -- Appendix 11. Cloth workers -- Appendix 12. Services -- Appendix 13. Horse killers -- Appendix 14. Farriers -- Appendix 15. Scienter with warnings -- Appendix 16. Scienter without warnings -- Appendix 17. Other Scienter writs -- Appendix 18. Innkeeper liability: London -- Appendix 19. Innkeeper liability -- Appendix 20. Jailers before 1348 -- Appendix 21. Jailers after 1348 -- Appendix 22. Indirect and consequential damages -- Appendix 23. Miscellaneous wrongs -- Appendix 24. Select repair writs -- Appendix 25. Select franchise writs.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Online resource (HeinOnline, viewed August 30, 2016).
English.
Keywords: Law -- England -- History; Great Britain -- Politics and government -- 1327-1377.; Black Death -- Social aspects -- England -- History; England -- Social conditions -- 1066-1485.; Law, Medieval; Great Britain -- Politics and government -- 1066-1485.; Grande-Bretagne -- Politique et gouvernement -- 1066-1485.; Droit -- Angleterre -- Histoire; Grande-Bretagne -- Politique et gouvernement -- 1327-1377.; Peste noire -- Aspect social -- Angleterre -- Histoire; Angleterre -- Conditions sociales -- 1066-1485.; Droit médiéval.; LAW -- Administrative Law & Regulatory Practice; Law -- England -- History; Black Death -- Social aspects -- England -- History; Law, Medieval; Great Britain -- Politics and government -- 1327-1377.; England -- Social conditions -- 1066-1485.; Black death -- Social aspects; Law; Law, Medieval; Politics and government; Social conditions; England; Great Britain; Rechtshervorming; Common law; Pest (ziekte); Droit -- Angleterre (GB) -- Histoire -- 14e siècle.; Peste -- Aspect social -- Angleterre (GB); Social Conditions -- history; Plague -- history; Legislation as Topic -- history; Law; Law -- Great Britain -- History; Great Britain -- Politics and government -- 1327-1377.; Social history -- Great Britain -- Medieval period, 1066-1485.; Black Death -- Social aspects -- Great Britain -- History; 1066-1485; Black Death -- Social aspects -- History -- England; England -- Social conditions -- 1066-1485; Geschichte -- 1348-1381; Great Britain -- Politics and government -- 1327-1377; Law -- History -- England; Law, Medieval; History